Phytoplankton Based Trophical State of the Tanjung Balam Lake in the Buluh Cina Village, Kampar District, Riau Province - Zein Lubis, Solat Adawiyah; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractMany activities in the Tanjung Balam Lake contribute the input of organic and anorganic matter that affects the nutrient concentration and increasing the growth of phytoplankton. A research about Trophic State of Tanjung Balam Lakeby Phytoplankton in Buluh Cina Village Kampar District Riau Province has been conducted in June-July 2019. The location of the water samples to measure water quality defined 3 stations, namely in the inlet, the curve of the lake, and in the end of the lake. In each station, there were 2 sampling points, namely in the surface (0.15 m) and 2 Secchi depth (0.90 m). Samplings were conducted 3 times at intervals of a week. Water quality parameters measured were temperature, transparency, depth, dissolved oxygen, CO2, pH, nitrate and phosphate contents. Results shown that there were 61 species of phytoplankton that were belonged to 7 classes, namely Chlorophyceae (23 species), Trebouxiophyceae (4 species), Zygnematophyceae (4 species), Euglenophyceae (14 species), Bacillariophyceae (12 species), Cyanophyceae (3 species), and Cryptophyceae (1 species). The phytoplankton abundance in the Tanjung Balam Lake was 606,144-982,688 cells/L. The most common type of phytoplankton present was Monoraphodium griffithii. Results shown that the temperature was 28-30.3oC, transparency was 49.7-54 cm, depth was 151-236.7 cm, pH was 5, dissolved oxygen was 4.03-6.57 mg/L, CO2 was 3.83-6.13 mg/L, nitrate was 0.016-0.03 mg/L, and phosphate was 0.083-0.108 mg/L. Based on the type and abundance of phytoplankton present, it can be concluded that the Tanjung Balam Lake can be categorized as mesotrophic.Keywords: Kampar River, Oxbow Lake, Mesotrophic, Phytoplankton abundance